2012
DOI: 10.1002/alr.21110
|View full text |Cite
|
Sign up to set email alerts
|

Is nasal packing necessary after septoplasty? A meta‐analysis

Abstract: Nasal packing after septoplasty does not show any postoperative benefits. Fibrin products show a possibility of decreasing postoperative bleeding. Routine use of nasal packing after septoplasty is not warranted. This is the first meta-analysis conducted on this topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 23 publications
5
36
1
2
Order By: Relevance
“…3,11 There are no general standards concerning the indications of nasal packing, the duration of the packing, or the type of material used. 3 Banglawala et al 13 performed a meta-analysis on the existing literature to evaluate the role of nasal packing after septoplasty. 3,12 As an alternative application to nasal packing, different forms of hemostatic suturing techniques of the nasal septum have been described.…”
Section: Discussionmentioning
confidence: 99%
“…3,11 There are no general standards concerning the indications of nasal packing, the duration of the packing, or the type of material used. 3 Banglawala et al 13 performed a meta-analysis on the existing literature to evaluate the role of nasal packing after septoplasty. 3,12 As an alternative application to nasal packing, different forms of hemostatic suturing techniques of the nasal septum have been described.…”
Section: Discussionmentioning
confidence: 99%
“…These are placed after surgery to prevent bleeding, septal hematoma, and septal abscess (13,14). Although the packs afford many advantages, they increase the risk of infection and cause pain (15). Complications include eustachian tube dysfunction, middle ear effusion, and obstruction of the larynx.…”
Section: Discussionmentioning
confidence: 99%
“…c, d Situation in 9 months after reconstruction of the columella and nasal septum Eur Arch Otorhinolaryngol operative nasal packing have demonstrated that packing of the nose causes significant discomfort and pain [7,8]. Furthermore, packing after septoplasty appears to increase the risk of post-operative infections [2]. Compared to postoperative nose packing, the pressure will likely be higher and the duration of packing might be longer with packing for epistaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Most publications focus on potential respiratory complications associated with nasal packing [1]. The risk of developing a local infection or toxic shock syndrome has been mentioned [2,3], although the routine use of antibiotics is not recommended [4]. Here, we describe four patients in whom balloon packing caused severe damage to nasal skin, mucosa or cartilaginous structures.…”
Section: Introductionmentioning
confidence: 99%